Reductive Cytochrome P450 Reactions and Their Potential Role in Bioremediation - Behrendorff, James B. Y. H. (Frontiers in Microbiology, 2021)
Cytochrome P450 enzymes, or P450s, are haem monooxygenases renowned for their ability to insert one atom from molecular oxygen into an exceptionally broad range of substrates while reducing the other atom to water. However, some substrates including many organohalide and nitro compounds present little or no opportunity for oxidation. Under hypoxic conditions P450s can perform reductive reactions, contributing electrons to drive reductive elimination reactions. P450s can catalyse dehalogenation and denitration of a range of environmentally persistent pollutants including halogenated hydrocarbons and nitroamine explosives. P450-mediated reductive dehalogenations were first discovered in the context of human pharmacology but have since been observed in a variety of organisms. Additionally, P450-mediated reductive denitration of synthetic explosives has been discovered in bacteria that inhabit contaminated soils. This review will examine the distribution of P450-mediated reductive dehalogenations and denitrations in nature and discuss synthetic biology approaches to developing P450-based reagents for bioremediation.